Evaluation of anthropometric indicators and food consumption in patients with type 2 diabetes mellitus - Araújo, Rafael do Nascimento; Aguiar, Antônio Henrique Braga Martins de; Azevedo, Yuri Sandro de Lima; Cantanhede, Lucas Antônio de Oliveira; Braga, Lorena Carvalho; Silva, Andréa Cristina Oliveira (Revista de Enfermagem da UFPI, 2022)
Objective: To evaluate the anthropometric indicators and food consumption of people with Type 2 Diabetes Mellitus treated at a Basic Health Unit in the city of São Luís, Maranhão. Methods: This is a cross-sectional and descriptive study with a quantitative approach conducted with 36 patients who have Type 2 Diabetes Mellitus, treated at a Basic Health Unit in the capital city of Maranhão. Semi-structured forms were used to collect sociodemographic and anthropometric data, as well as related to eating habits. The analyses were performed using descriptive statistics, with data represented as mean, frequency and their respective standard deviations, in addition to Pearson’s correlation test between the quantitative variables. Results: The sample was mostly represented by women (54.4%), older adults (59.6%), sedentary people (63.1%), who had high abdominal obesity (80.4%), ingested a low amount of fiber (93.5%) and consumed a large amount of protein (67.4%), saturated fat (69.6%) and sucrose (57.5%). Conclusion: Factors such as inadequate weight and unregulated eating habits can represent risks for glycemic control and contribute to worsening of Diabetes Mellitus. Descritores: Diabetes mellitus. Estado nutricional. Consumo de alimentos.